Numerical simulation of the water bubble rising in a liquid column using the combination of level set and moving mesh methods in the collocated grids - Bu, Lin (2013)
The proper interpretation of bubble rising in a liquid column is critical in the investigation of the water–vapour two phase flow and heat transfer. In this paper, the bubble behaviours are studied using the combination of Level Set Method (LSM) and moving mesh method in a collocated grid. Level set method is used to track the interface of the bubble, which has many advantages over other interface tracking methods such as it can accurately calculate the curvature of the interface and easily expand to three dimensions. But if the uniform grid was adopted, the bubble interface cannot adapt well with the grid which may cause great numerical errors. Hence, moving mesh method is implemented in this paper to increase the numerical accuracy. The numerical model developed in this paper is benchmarked with the experimental data. The results show that the grid distributions used in this paper can catch the interface continuously in space and time. The process of bubble starting from deformation until break into three small bubbles is clearly shown from the numerical results. In addition, the changing of bubble behaviour with the temperature and pressure is also investigated. It is found that as the pressure and temperature increase, the deformation process will slow down and this tendency accelerates.